Topological Engineering of Pt-Group-Metal-Based Chiral Crystals toward High-Efficiency Hydrogen Evolution Catalysts - Yang, Qun; Li, Guowei; Manna, Kaustuv; Fan, Fengren; Felser, Claudia; Sun, Yan (Advanced Materials, 2020)
It has been demonstrated that topological nontrivial surface states can favor heterogeneous catalysis processes such as the hydrogen evolution reaction (HER), but a further decrease in mass loading and an increase in activity are still highly challenging. The observation of massless chiral fermions associated with large topological charge and long Fermi arc (FA) surface states inspires the investigation of their relationship with the charge transfer and adsorption process in the HER. In this study, it is found that the HER efficiency of Pt-group metals can be boosted significantly by introducing topological order. A giant nontrivial topological energy window and a long topological surface FA are expected at the surface when forming chiral crystals in the space group of P213 (#198). This makes the nontrivial topological features resistant to a large change in the applied overpotential. As HER catalysts, PtAl and PtGa chiral crystals show turnover frequencies as high as 5.6 and 17.1 s−1 and an overpotential as low as 14 and 13.3 mV at a current density of 10 mA cm−2. These crystals outperform those of commercial Pt and nanostructured catalysts. This work opens a new avenue for the development of high-efficiency catalysts with the strategy of topological engineering of excellent transitional catalytic materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: chiral crystals; electrocatalysts; hydrogen evolution; Pt-group metals; topological engineering